Pengaruh senam aerobik low impact terhadap peningkatan kebugaran jasmani pada siswa - Waluyo, Waluyo (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
The importance of physical fitness as one of the supporting factors for student activities needs to be considered. Importance of physical fitness requires improvement and defense in its condition. Providing physical activity is one of the factors that can improve students' physical fitness. This study aimed to determine the effect of low-impact aerobic gymnastics on improving student fitness. This research method uses a pre-experimental design using one group pretest-posttest without using variable control. The study subjects used the Proportionate stratified random sampling technique by taking male students aged 13-15 in junior high school. The research instrument uses the Indonesian Physical Fitness Test to measure strength, speed, endurance, strength, and power. Data analysis techniques use normality and homogeneity prerequisite tests, and to determine the influence on variables using t-tests, data analysis procedures use SPSS 25. The results of the study said The results of calculations using the t-test approach method obtained 0.841. This result is greater than Ttabel, which amounted to 1,701 because the analysis results said there was a significant effect of low-impact aerobic exercise on physical fitness. This study concludes that low-impact aerobic exercise can improve students' physical fitness.